2017
DOI: 10.1371/journal.pone.0171479
|View full text |Cite
|
Sign up to set email alerts
|

Eupatilin exerts neuroprotective effects in mice with transient focal cerebral ischemia by reducing microglial activation

Abstract: Microglial activation and its-driven neuroinflammation are characteristic pathogenetic features of neurodiseases, including focal cerebral ischemia. The Artemisia asiatica (Asteraceae) extract and its active component, eupatilin, are well-known to reduce inflammatory responses. But the therapeutic potential of eupatilin against focal cerebral ischemia is not known, along with its anti-inflammatory activities on activated microglia. In this study, we investigated the neuroprotective effect of eupatilin on focal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 39 publications
(70 reference statements)
2
28
0
Order By: Relevance
“…Activated microglia may contribute to cerebral I/R injury via phagocytosis and elaboration of neuroinflammatory mediators toxic to cells 29 . Studies have shown that decreased microglial activation in the ischemic hemisphere of the brain is associated with marked reduced cerebral I/R injury 30 , 31 . In the present study, post-ischemic microglia activation was significantly attenuated after chronic low-dose consumption of red wine and ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…Activated microglia may contribute to cerebral I/R injury via phagocytosis and elaboration of neuroinflammatory mediators toxic to cells 29 . Studies have shown that decreased microglial activation in the ischemic hemisphere of the brain is associated with marked reduced cerebral I/R injury 30 , 31 . In the present study, post-ischemic microglia activation was significantly attenuated after chronic low-dose consumption of red wine and ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…was administered twice a day at 12-h intervals on the second and third day after tMCAO challenge. Brain sections were prepared for Iba1/BrdU immunofluorescence as described previously [ 18 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…This transcription factor empowers the generation of proinflammatory enzymes and cytokines, including tumor necrosis factor-α (TNF-α), inducible nitric oxide synthase (iNOS), and intracellular adhesion molecule-1 (ICAM-1) ( Zhang et al, 2016 ). These events amplify the inflammatory cascade and trigger the recruitment of neutrophils, thereby exacerbating the ischemic insult ( Cheng and Lee, 2016 ; Sapkota et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%